Comparison between published clinical success of direct resin composite restorations in vital posterior teeth in 1995–2005 and 2006–2016 periods. (19th April 2017) - Alvanforoush, N; Palamara, J; Wong, RH; Burrow, MF
Abstract: Composites are increasing in popularity as restorative materials. This growing role indicates the necessity of studies on their clinical outcome. In this study, clinical studies published on the performance of posterior composite restorations were included except those of less than a 24‐month assessment period. Results of non‐vital, anterior or primary teeth and cervical single‐surface restorations were also excluded. Records about composite type, number of final recall restorations, failure/survival rate, assessment period and failure reasons were analysed for each decade. Overall survival/failure rates for studies in 1995–2005 were 89.41%/10.59% and for 2006–2016 were 86.87%/13.13%, respectively. In 1995–2005, the reasons for failure were secondary caries (29.47%) and composite fracture (28.84%) with low tooth fracture (3.45%) compared with reasons of failure in 2006–2016, which were secondary caries (25.68%), composite fracture (39.07%), and tooth fracture (23.76%). An increase in incidence of composite fracture, tooth fracture and need for endodontic treatment as failure reasons was noted in the latter decade in addition to a decrease in secondary caries, postoperative sensitivity, unsatisfactory marginal adaptation and wear. The overall rates of failure showed little difference, but the causes showed a notable change. This is believed to be a reflection of increased use of composites for larger restorations and possibly changes of material characteristics.